Lean for Life : the cookbook : the Louise Parker method - Parker, Louise (Personal trainer) (London : Mitchell Beazley, 2020)
This year, start a new you eating plan you can maintain for life. Louise Parker shows you how the A-Listers do it. Don't be fooled by vague promises of organic 'clean' eating. Teach yourself to eat beautifully, eat lean and transform your body forever. This cookbook not only contains over 120 fuss-free recipes; it arms you with the knowledge to create hundreds of variations so you will never get bored.
Text on inside cover.
Includes index.
Keywords: Reducing diets -- Recipes; Food and Drink